Effectiveness of Policy Implementation of Covid-19 Social Assistance for Persons with Disabilities in DKI Jakarta Province - Zahirman, Ari; Juwono, Vishnu (Graduate Program Magister Manajemen Pendidikan, 2023)
Covid-19 has become a non-natural disaster that has hit the whole world. The Covid-19 pandemic not only has an impact on health but also has an impact on the socio-economic conditions of the community. Persons with disabilities are a group of people who are vulnerable to the dangers of covid and its socio-economic impacts. Policies that favor groups with disabilities are needed to help fulfill and equal rights as citizens. This research specifically discusses the implementation of social assistance policies for persons with disabilities in DKI Jakarta Province. This issue is considered important because DKI Jakarta is the epicenter of the spread of Covid-19 and has become a reference for controlling the spread and economic recovery for other regions. This study uses a policy implementation model that is seen from the dimensions of the level of ease or difficulty of problems to be overcome, the capacity of the structure of the implementation process, and the identification of external variables that affect the implementation process. The research method in this study uses qualitative by exploring secondary data as a data base for analysis carried out by reducing data, presenting data and drawing conclusions. The results of this study are that social assistance policies for persons with disabilities are quite effective for short-term policies in the context of economic protection during a pandemic, but not effective enough as long-term policies for economic recovery. Welfare policy for disabilities is a systemic policy, so it requires the involvement of many actors and aspects to produce policies that are substance and based on outcomes.